Integrating Media-Assisted Instruction to Enhance English Language Skills within a School English Community - Eppendi, Jhoni; Vega, Nofvia De (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service project at Muhammadiyah Senior and Junior High Schools in Tarakan, North Kalimantan, sought to resolve the issue of low student engagement and English language proficiency within the English Community (EC) program, which had previously employed conventional teaching methods. The primary objective was to improve learning outcomes by incorporating media-assisted instruction. Comprehensive needs assessments, stakeholder engagement, and collaborative planning with school principals, EC coordinators, and teachers comprised the project. Educators were instructed on the effective utilization of multimedia resources. Iterative feedback and continuous improvement were incorporated into the implementation. The findings indicated a 20% enhancement in students' English proficiency and a 25% increase in motivation and engagement. These results emphasize the significance of continuous evaluation, student involvement, capacity building, needs-based customization, and collaborative design in educational interventions, which result in substantial enhancements in language learning and overall student participation.